Ethanol extract of waste potato peels for corrosion inhibition of low carbon steel in chloride medium - Shekhar C.; Jaiswal A.; Ji G.; Prakash R. (My University, 2025)
Corrosion of low carbon steels is a big constraint in their smooth use for engineering applications. Corrosion not only destroys their designed properties but also harms their physical appearance. Several researchers are working to minimize the effect of corrosion on low carbon steel. In this regard, they have consumed a lot of synthetic and natural materials till date. Nowadays, researchers are showing their trust on natural materials for corrosion inhibition application due to their easy availability, negligible toxicity and easy synthesis process as well as eco-friendly nature. It is an established fact that waste natural materials (WNMs) like banana peels have very high potential for being used in corrosion inhibition application due to their bioactive contents. However, WNMs have not been explored frequently by the researches despite their supreme technical and economical importance in corrosion inhibition. In this work, ethanol extract of waste potato peels is used for corrosion inhibition of low carbon steel in 0.5 M NaCl. The inhibition properties of the extract are determined by weight loss measurements, open circuit potential (OCP) curves, electrochemical impedance spectroscopy (EIS), Tafel polarization curves and linear polarization resistance (LPR) techniques. Results show that maximum corrosion inhibition efficiency of 70% has been achieved using 1000 mg L-1of the extract. Scanning electron microscopy (SEM) and energy dispersive X-RD Spectroscopy (EDX) has also shown that the extract has successfully protected low carbon steel in 0.5 NaCl. © 2021 Elsevier Ltd. All rights reserved.